Pemberdayaan Ibu-Ibu untuk Penguatan Ekonomi Keluarga Melalui Pelatihan Pembuatan Kripik Tempe di Desa Penantian Kab Ogan Komering Ulu Sumatera Selatan - Andri Irawan; Dyah Ayu Putriani; Nourma Wulanda; Dahlia Dahlia; Tati Herlina; Novie Al Muhairiah; Agus Kurniawan; Astrina Utami (BADAN PENERBIT STIEPARI PRESS, 2025)
This community service activity aims to empower mothers in Penantian Village, Ogan Komering Ulu Regency, South Sumatra, through training in making tempeh chips as an effort to strengthen the family economy. The main problems faced by the local community are limited food processing skills and low family income. The implementation method includes counseling, demonstration of making tempeh chips, direct practice, packaging assistance, and introduction to simple marketing strategies. The results of the activity showed that participants gained new knowledge and skills in producing tempeh chips hygienically and with sales value. This training also increased the motivation and confidence of mothers to start home businesses. It is hoped that this program can be the first step in creating sustainable independent business opportunities and contribute to improving the economic welfare of families in Penantian Village